The effect of IL17 and IL23 inhibitors on hematological parameters and C-reactive protein in psoriasis patients - Esen, Mustafa (Taylor & Francis Ltd, 2024)
Introduction: In the quest for objective biomarkers for psoriasis, the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), C-reactive protein (CRP), and mean platelet volume (MPV) have been used to assess disease severity, treatment efficacy, and follow-up in psoriasis, and their relationship with the Psoriasis Area Severity Index (PASI) has been investigated.Purpose: The evaluation of pre-treatment, 3rd and 6th-month levels of NLR, PLR, MPV, and CRP along with PASI scores in psoriasis patients treated with secukinumab, ixekizumab, risankizumab, and guselkumab.Materials and Methods: In our study, 83 patients aged 18 and over, who were followed up with moderate-severe plaque type psoriasis vulgaris and psoriatic arthritis and received secukinumab, ixekizumab, risankizumab, and guselkumab treatment in the chronic skin diseases clinic of Firat University Faculty of Medicine Hospital between January 2019 and 2023, were evaluated retrospectively.Results: Post-treatment leukocyte, neutrophil, lymphocyte, platelet, CRP, and PASI values were statistically significantly lower in all biological agent groups and all patients. The post-treatment NLR value was statistically significantly higher in all patients and in the group using ixekizumab. The post-treatment PLR value was statistically significantly higher in the group using guselkumab and ixekizumab and in all patients. The post-treatment MPV was statistically significantly higher in all patients and in the group using secukinumab. No correlation was found between post-treatment PASI and other values (p > 0.05). There was no statistically significant difference between the post-treatment 6-month values among all biological agent groups. The effects of different drugs on outcomes after treatment were found to be similar (p > 0.05).Conclusion: Our study supports the view that MPV and CRP can be used in patients with psoriasis using IL17 and IL23 inhibitors, while NLR and PLR parameters derived from blood count may not be used to evaluate treatment response, contrary to other studies.
Keywords: Psoriasis; neutrophil-lymphocyte ratio; platelet-lymphocyte ratio; mean platelet volume; c-reactive protein